Analisis Bauran Promosi yang Paling Berpengaruh terhadap Keputusan Mahasiswa Baru dalam Memilih Universitas Sarjanawiyata Tamansiswa - Imas nursiwan Dono (Jurnal Manajemen Bisnis Eka Prasetya, 2021)
The purpose of this study was to analyze the Influence of Promotion Mix which Most Influences on Student Decisions in Choosing Sarjanawiyata Tamansiswa University. The research methodology used is descriptive quantitative method, the unit of analysis in this study is Sarjanawiyata Tamansiswa University and the observation unit is the students of the Sarjanawiyata Tamansiswa University. The population in this study were 4,270 respondents from Sarjanawiyata Tamansiswa University. The technique for determining the number of samples used in this study is the Slovin formula and totals 135 respondents. The research method used is data collection techniques through questionnaires which are carried out systematically in accordance with the research objectives. The analysis method used to solve problems and prove the hypothesis is descriptive analysis and regression analysis. This analysis includes validity and reliability tests, classic assumption tests, multiple linear regression analysis, hypothesis testing through the F test and t test, the coefficient of determination (R2) and thetest Standardized Beta Coefficient. The results of the F test show that simultaneously Advertising, Personal Selling, Sales Promotion and Publicity have a positive and significant effect on student decisions in choosing Sarjanawiyata Tamansiswa University. The results of the t test partially show that the Advertising variable and the Sales Promotion variable have a positive and significant effect on student decisions in choosing Sarjanawiyata Tamansiswa University, the Personal Selling variable and the Publicity variable have no positive or significant effect on student decisions in choosing Sarjanawiyata Tamansiswa University. The results of the coefficient of determination (R2) test show that student decisions are influenced by the variables of Advertising, Personal Selling, Sales Promotion, and Publicity, while the rest is explained by other variables not discussed in this study. Judging from the results of Standarized Beta Coefficient, it shows that the most dominant variable in this study and the most influential on student decisions is advertising.